Spontaneous Fundal Uterine Rupture in a Pregnant Woman at 32 Weeks Gestation who had Two Previous Cesarean Sections - Kaba, Metin; Öksüzoğlu, Ayşegül; Timur, Hakan; Akbaba, Eren; Kaba, Gökçen; Üstün, Yaprak Engin (Gynecology Obstetrics & Reproductive Medicine, 2017)
Spontaneous uterine rupture during pregnancy can cause severe complications, even maternal and fetal demise. We report successful management of a spontaneous fundal uterine rupture in a 32 week pregnant who had undergone two previous cesarean sections due to preterm delivery. We explain causes of spontaneous uterine rupture and the management of this rare event in the presented case report.